2017
DOI: 10.1080/13557858.2017.1283393
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous bodies, uncertain diseases: knowledge of cervical cancer in Papua New Guinea

Abstract: Local understandings of cervical cancer reflected the limitations of Tok Pisin as a lingua franca as well as the wider uncertain biomedical environment where diagnoses are assembled and shared. There is a clear need to improve understanding of the female reproductive organs in order that people, women in particular, can be better informed about cervical cancer and ultimately better receptive to intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
5
14
0
Order By: Relevance
“…We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS. In concurrence with other studies, our respondents considered CCS as an intervention for STI management (27,(56)(57)(58). A misconception was found concerning the role of cleanliness and hygiene to prevent STIs (HPV infection specifically) and cervical cancer, and similar findings have been reported by other studies (33,52).…”
Section: Discussionsupporting
confidence: 89%
“…We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS. In concurrence with other studies, our respondents considered CCS as an intervention for STI management (27,(56)(57)(58). A misconception was found concerning the role of cleanliness and hygiene to prevent STIs (HPV infection specifically) and cervical cancer, and similar findings have been reported by other studies (33,52).…”
Section: Discussionsupporting
confidence: 89%
“…We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS. In concurrence with other studies, our respondents considered CCS as an intervention for STI management (25,(50)(51)(52). A misconception was found concerning the role of cleanliness and hygiene to prevent STIs (HPV infection specifically) and cervical cancer, and similar findings have been reported by other studies (31,46).…”
Section: Discussionsupporting
confidence: 89%
“…We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS. In concurrence with other studies, our respondents considered CCS as an intervention for STI management (27,(57)(58)(59). A misconception was found concerning the role of cleanliness and hygiene to prevent STIs (HPV infection speci cally) and cervical cancer, and similar ndings have been reported by other studies (33,53).…”
Section: Discussionsupporting
confidence: 89%